A new side of sarcoidosis: medication and hospitalization use in a privately insured patient population - Low, Derek; Simpson, Kit N.; Rissmiller, Richard; James, Ennis (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Objective: This study describes patterns of medication prescriptions for sarcoidosis patients in a large commercially insured U.S. population, with specific focus on prescribing practices across medical specialties and their associated hospitalization risk. Methods: Using the Marketscan Database we selected adult patients with a diagnosis of sarcoidosis by ICD-9 code during the 2012 calendar year. Differences in prescribing practices were evaluated between provider types. A multivariate model controlling for age, sex, and region assessed hospitalization risk associated with provider type, prednisone dose, and use of non-steroid sarcoidosis medications. Results: Using the described criteria, 11,042 total patients were identified. A majority were female, mean age 49.3 years. Of these, 1,792 (16.2%) had one or more hospital admissions (mean 1.6, SD 1.3) with a mean length of stay of 8.1 days (SD 14.5). 25.5% of patients were prescribed prednisone with a 1 year mean cumulative dose of 250mg. Pulmonary/Rheumatology providers prescribed the highest cumulative prednisone dose (961 mg) and were more likely to prescribe methotrexate and monoclonal antibody medications. Sarcoidosis patients receiving a cumulative prednisone dose >500 mg had an increased risk for hospitalization (OR 2.512, 2.210-2.855), while those prescribed methotrexate and azathioprine had decreased risk (OR 0.633, 0.481-0.833 and 0.460, 0.315-0.671). Monoclonal antibody use was associated with increased OR for hospitalization at 1.359. Conclusion: Sarcoidosis patients treated by subspecialists were more likely to receive higher doses of prednisone and non-steroid sarcoidosis medications. Higher doses of prednisone and monoclonal antibody use were associated with higher hospitalization risk while methotrexate and azathioprine were associated with lower hospitalization risk.